Review on Efficacy of Lumber Traction on Low Back Pain - Rahman, Md Shahidur; Uddin, Mohd Taslim; Ahsanulla, Md (Journal of Medicine, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Back pain is a problem to health professionals and to the society. Low back pain is now one of the most common reasons for work loss, health care use and sickness benefit. There are many causes of low back pain. Non-specific mechanical low back pain is most common. Treatment options include surgical and conservative. Conservative treatment is usually given with analgesics, thermo therapy and lumber traction. Treatment plan and referral is made on the basis of judgment on clinical findings. The aim of the present review was to assess the efficacy of traction for LBP patients with or without radiating pain. To reflect clinical practice, we need to understand the clinical parameters and treatment regimes being used by clinicians, and these must be addressed before a trial can be designed to look further at the effectiveness of traction for LBP with or without radiating pain. The evidence for the use of traction in LBP remains inconclusive because of the continued lack of methodological rigor and the limited application of clinical parameters as used in clinical practice. Keywords: Low back pain, Lumber traction, Efficacy. DOI = 10.3329/jom.v8i2.1412 J MEDICINE 2007; 8 : 69-73